Seasonal and Regional Differences in Economic Benefits of Turkey Hunting. (20th May 2020) - Chapagain, Binod P.; Poudyal, Neelam C.; Joshi, Omkar; Watkins, Cristina; Applegate, Roger D.
ABSTRACT: Wild turkey ( Meleagris gallopavo silvestris ; hereafter, turkey) hunting is a popular outdoor recreation activity in many states, including Tennessee, USA. Despite its cultural and social significance, economic benefits associated with turkey hunting are largely unknown. Past economic studies either focused on other big game species or provided generic value for big game, and do not offer benefit estimates specific to turkey. We estimated a demand model for turkey hunting trips in Tennessee and quantified per‐trip and statewide aggregate value of turkey hunting. We compared the net economic value of turkey hunting trips between hunting seasons (autumn and spring) and wildlife management regions that differ in many aspects including turkey population, hunting regulations, etc. Per person per trip value of turkey hunting ranged between US$34 and US$90 depending on the modeling assumption regarding hunters' opportunity cost of time. Moreover, estimated value differed among regions and between hunting seasons, with the value of a turkey‐hunting trip in the spring season being twice that of the autumn season. Many states in southern United States, including Tennessee, have recently experienced declines in turkey populations and are in need of economic justifications for investment in research and management. Our results are useful to wildlife agencies in characterizing economic benefits of turkey hunting and evaluating the welfare implications of regulations (e.g., closure, reduction in season length) restricting or expanding hunting opportunities. © 2020 The Wildlife Society. Abstract : We estimated a demand model for turkey hunting trips in Tennessee, USA, and quantified per‐trip and statewide value of turkey hunting. The estimated value differed among management regions and hunting seasons, with the value of turkey‐hunting trips in the spring season being twice that of the fall season.